Women and al Qaeda part 1 welcome and opening remarks panel 1 - Jebsen Center for Counter Terrorism Studies (Tufts Archival Research Center, 2020)
This video was transcribed using WhisperX AI, run locally. It has been reviewed by a human editor. Please contact TARC for further information.